Reconfiguring Home Through Travel: The Poetics of Home, Displacement and Travel in Agha Shahid Ali’s Poetry - Antara Chatterjee (Humanities, 2020)
This article seeks to examine how the Kashmiri-American poet Agha Shahid Ali explores and rethinks ideas of “home” and travel in his poetry. Ali’s poetry is a layered affective terrain in which his complex, entangled emotions surrounding home, exile, nostalgia, displacement, and travel play out. I argue that Ali’s verse, through multiple journeys ranging over locations, languages, cultures, and literary terrain, interrogates and collapses the boundaries between the “home” and the world. I read his poetry as voicing the “disturbed” and displaced home of Kashmir, while simultaneously distilling a “re-homing” desire. Such an impulse reconfigures and reimagines the home through the inhabiting and repeated “homing” of multiple, “foreign” locations. Poetic travel across geographic and literary terrain, in Ali’s oeuvre, thus speaks to the fraught and complex nature of the “home” in postcolonial and diasporic contexts, while remapping the home through the “re-homing” of the “foreign”. Arguing that “travel” is a means of negotiating and rethinking the “home” in Ali’s poetry, the article examines the intermeshed and dialogic relationship between home and travel that imbues his verse. Focusing particularly on poetic experimentation as a mode of travel, it aims to show how such literary travel makes new homes, while remembering and articulating Ali’s lost homes.